PROFIL KEMAMPUAN NUMERASI SISWA SMA DI BANGKA DALAM MENYELESAIKAN PERMASALAHAN BERBASIS ASESMEN KOMPETENSI MINIMUM DARI SEGI PENALARAN ADAPTIF [PROFILE OF THE NUMERACY ABILITY OF HIGH SCHOOL STUDENTS IN BANGKA IN SOLVING PROBLEMS BASED ON MINIMUM COMPETENCY ASSESSMENT IN TERMS OF ADAPTIVE REASONING] - Pratiwi, Indah Riezky; Novitasari, Novitasari; Sari, Elisa Mayang (JOHME: Journal of Holistic Mathematics Education, 2024)
Numeracy and literacy are the focus of Indonesia's education system. This is evident from the implementation of the Minimum Competency Assessment (AKM), which has been part of the national annual assessment since 2021. The results are analyzed and reflected upon to assess the quality of education in implementing schools. Students' numeracy skills can improve if they use reasoning to solve problems. Reasoning connects the concepts they hold with the context of the problem at hand. Reasoning results are used to interpret, analyze, and make decisions. The reasoning in question focuses on adaptive reasoning (reflection, explanation, and justification). Research was conducted to describe the adaptive reasoning of high school students through the answers of students who participated in a reasoning competition. The instrument used is a numeracy test. This research is qualitative with descriptive methods. Analysis was conducted on the three student answers that obtained the highest scores (purposive sampling) and focused on the fertilizer theme. This theme is presented in graphic form as a stimulus with two questions that students need to answer. The data analysis technique in this research involved reducing the data. The result obtained was that one student used aspects of adaptive reasoning (reflection, explanation, and justification) completely in answering questions. This indicates that this student can solve problems using adaptive reasoning. This student is said to have good numeracy skills because they can use adaptive reasoning.BAHASA INDONESIA ABSTRACT: Literasi dan numerasi menjadi salah satu fokus pada dunia pendidikan di Indonesia. Hal ini terlihat dari pelaksanaan Asesmen Kompetensi Minimum (AKM) yang menjadi bagian dari asesmen nasional dilakukan secara berkala sejak tahun 2021. Hasilnya dianalisis dan direfleksikan menjadi mutu pendidikan dari sekolah yang melaksanakan. Kemampuan numerasi siswa dapat dikatakan baik jika siswa dapat menggunakan nalarnya untuk menyelesaikan permasalahan. Penalarannya digunakan untuk mengaitkan antara konsep yang dimiliki dengan konteks masalah yang dihadapi. Hasil penalaran dimanfaatkan untuk menginterpresi, menganalisis, sampai mengambil keputusan. Penalaran yang dimaksud berfokus pada penalaran adaptif (reflecting, explaining, dan justifying). Penelitian dilakukan untuk mendeskripsikan penalaran adaptif siswa SMA melalui jawaban siswa yang mengikuti lomba nalaria. Intrumen yang digunakan adalah tes numerasi. Jenis penelitian pada penelitian ini adalah kualitatif dengan metode deskriptif. Analisis dilakukan pada tiga jawaban siswa yang memperoleh skor tertinggi (pusposive sampling) dan berfokus pada tema pupuk. Tema ini disajikan dalam bentuk grafik sebagai stimulus dan dua soal yang perlu dijawab siswa. Teknik analisis data pada penelitian ini dengan mereduksi data. Hasil yang diperoleh adalah satu siswa yang menggunakan aspek penalaran adaptif (reflecting, explaining, dan justifying) secara utuh dalam menjawab soal. Hal ini mengindikasikan bahwa siswa ini dapat dikatakan mampu menyelesaikan masalah dengan menggunakan penalaran adaptifnya. Siswa ini dikatakan memiliki kemampuan numerasi yang baik karena mampu mempergunakan penaralan adaptifnya.